Utilization of palm oil sludge in poultry diet: 2. Dried palm oil sludge and its fermented product for growing drakes - Arnold P Sinurat; I.A.K Bintang; T Purwadaria; T Pasaribu (Jurnal Ilmu Ternak dan Veteriner, 2001)
Inclusion limit of palm oil sludge (POS) in poultry diet varies according to processing, and species or strain of the animal. Therefore, an experiment was conducted to study the utilization of fermented (FPOS) and non-fermented palm oil sludge (POS) for growing drakes. A number of 224 one week-old male ducklings were randomly distributed into 7 dietary treatments, with 4 replicates and 8 ducklings for each replicate. The dietary treatment consists of 2 kinds of feedstuffs (POS and FPOS) with 3 levels (5, 10, and 15%) and one control diet consisting neither POS nor FPOS. All diets were formulated with similar nutrient contents and meet the requirement of growing duckling and fed to 8 weeks old. The results showed that at the first week of the trial, feeding of POS or FPOS significantly (P<0.05) depressed growth of the ducklings, although the feed consumption was higher than the control. However, overall performances (body weight, feed consumption and feed conversion) of the ducklings, carcass yield, liver weight, gizzard weight and abdominal fat weight measured at the end of the trial were not significantly (P>0.05) affected by the dietary treatments. Therefore, it is concluded that it is safe to include POS or FPOS up to 15% in the diet of growing ducklings.   Key words: Palm oil sludge, fermentation, ducks, growth